Terrestrial invertebrates as bioindicators in restoration ecology: A global bibliometric survey. (June 2021) - Borges, Felipe Luis Gomes; Oliveira, Maxwell da Rosa; de Almeida, Tiago Conde; Majer, Jonathan D.; Garcia, Letícia Couto
Highlights: Globally, our knowledge is focused on a limited set of taxonomic groups. We know more about small and young areas, degraded by mining or agriculture. Planted or seeded areas monitored by diversity or richness indexes are the most common investigations. Groups evaluated and functional group approaches have been increasing in recent years. Incomplete-Puzzle hypothesis can be a more realistic approach in restoration scenarios. Abstract: Biodiversity promotion activities, such as ecological restoration, are recognized as instruments to arrest and mitigate the diminishing health of ecosystems. The restoration of fauna is a fundamental component of this process but, despite this, there are few studies that compile and discuss the knowledge produced on this topic. Hence, by seeking a general understanding of what we currently know about terrestrial invertebrates as bioindicators in restored ecosystems, the present work sought to organize knowledge in such a way as to indicate gaps and opportunities for both researchers and restorers. To this end, we searched for topics associated with restoration ecology in the Web of Science database, identifying which invertebrate groups have been studied in relation to intrinsic characteristics of ecological intervention, including type of biome, type of disturbance, restoration technique, age, project size, and indices used. We found 154 studies published between 1995 and 2018: 93.5% of which were from 2002 onwards. We detected a growing number of studies and a tendency to evaluate functional groups. Moreover, there was a high concentration of studies within a few taxonomic groups, notably Hymenoptera (Formicidae), Coleoptera, and Lepidoptera. Many of the restoration scenarios are poorly studied, for example, in temperate coniferous forests or taiga biomes, previous disturbances caused by pollution or urbanization, under certain restoration techniques such as brushwood transposition, and investigations in large or old areas. There was also a paucity of information concerning community or population-level measures of restoration success, such as the structure of communities, biomass, and dominance. We discuss some consequences of these knowledge gaps. Finally, we indicate which taxonomic groups have been evaluated in relation to each restoration characteristic considered, resulting in guidance for those wishing to engage in research and monitoring of such organisms during the restoration process.